An Invitation to Health: Taking Charge of Your Health, 19th Edition - Dianne Hales (Cengage Learning, 2020)
From physical and mental to social and sexual, Dianne Hales' AN INVITATION TO HEALTH: TAKING CHARGE OF YOUR HEALTH helps students achieve a healthier lifestyle now and in the future. The 19th Edition covers new research on such topics as happiness and health, current statistics on life expectancy and death rates, mental health and anxiety, screen time and online presence, Dietary Guidelines, immunization, sleep habits, stress levels, safe sex practices, substance abuse (including new information on the opioid epidemic), dubious diets and trendy foods, fitness monitors, and vaping and cannabinoids. It also addresses healthy living on a budget, preventive measures and practical strategies that turn small changes into big benefits.